Development of Scientific and Natural Competence of Technology Teachers in the System of Postgraduate Education by Means of Information and Communication Support - Kashyna, Ganna; Nazarova, Karina; Burak, Valentina (Journal of Education, Technology and Computer Science, 2019)
The research deals withthe analysis of the results of experimental work on the problem of development of technology teachers’scientific and natural competence in the postgraduate education system in the conditions of modern processes of education informatization. Itdescribes the main results of the technology teachers’ scientific and naturaltraining study in the postgraduate education system by means of information and technological support.On this basis it is concluded that the effective knowledge and skill masteringis provided dueto the usageof information and technological support in the postgraduate pedagogical education system.